Plant-Derived Chimeric Virus Particles for the Diagnosis of Primary Sjögren Syndrome - Tinazzi, Elisa; Merlin, Matilde; Bason, Caterina; Beri, Ruggero; Zampieri, Roberta; Lico, Chiara; Bartoloni, Elena; Puccetti, Antonio; Lunardi, Claudio; Pezzotti, Mario; Avesani, Linda (Frontiers in Plant Science, 2015)
Plants are ideal for the production of protein-based nanomaterials because they synthesize and assemble complex multimeric proteins that cannot be expressed efficiently using other platforms. Plant viruses can be thought of as self-replicating proteinaceous nanomaterials generally stable and easily produced in high titers. We used Potato virus X (PVX), chimeric virus particles, and Cowpea mosaic virus, empty virus-like particles to display a linear peptide (lipo) derived from human lipocalin, which is immunodominant in Sjögren’s syndrome (SjS) and is thus recognized by autoantibodies in SjS patient serum. These virus-derived nanoparticles were thus used to develop a diagnostic assay for SjS based on a direct enzyme linked immunosorbent assay format. We found that PVX-lipo formulations were more sensitive than the chemically synthesized immunodominant peptide and equally specific when used to distinguish between healthy individuals and SjS patients. Our novel assay therefore allows the diagnosis of SjS using a simple, low-invasive serum test, contrasting with the invasive labial biopsy required for current tests. Our results demonstrate that nanomaterials based on plant viruses can be used as diagnostic reagents for SjS, and could also be developed for the diagnosis of other diseases.